2017
DOI: 10.1111/gtc.12479
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma pigmentosum group C protein interacts with histones: regulation by acetylated states of histone H3

Abstract: In the mammalian global genome nucleotide excision repair pathway, two damage recognition factors, XPC and UV-DDB, play pivotal roles in the initiation of the repair reaction. However, the molecular mechanisms underlying regulation of the lesion recognition process in the context of chromatin structures remain to be understood. Here, we show evidence that damage recognition factors tend to associate with chromatin regions devoid of certain types of acetylated histones. Treatment of cells with histone deacetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 83 publications
(85 reference statements)
3
23
0
Order By: Relevance
“…A recent report demonstrated a direct interaction between histone and XPC, through which histone deacetylation modulates the localization and functions of XPC in the process of DNA damage recognition for NER 48 . Here we show that DOT1L/H3K79 methylation also plays the crucial role on the regulation of XPC recognition of DNA lesion and modulates the interaction between XPC and histones.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report demonstrated a direct interaction between histone and XPC, through which histone deacetylation modulates the localization and functions of XPC in the process of DNA damage recognition for NER 48 . Here we show that DOT1L/H3K79 methylation also plays the crucial role on the regulation of XPC recognition of DNA lesion and modulates the interaction between XPC and histones.…”
Section: Resultsmentioning
confidence: 99%
“…A particular difference is that XP patients show a high frequency of skin cancer, while TTD and CS patients have a low incidence of tumors; also, the CS syndrome includes developmental and neurological abnormalities [ 21 ]. In view of the complex genomics of these several syndromes, it is not surprising that there are conflicting reports on the effects of HDAC inhibition on the efficiency of NER among these different but related pathologies [ 23 27 ]. In the context of this present study, it is primarily of interest that PBZ shows considerable concurrence with classical HDAC inhibitors in regard to gene enrichment scores for UVC-related gene signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Because 6–4PPs are shown to be generated by UV irradiation in chromatin in a relatively random manner [46], this fact strongly suggests existence of unprecedented molecular mechanisms that enable alteration of chromatin structures prior to lesion detection by XPC. We have recently reported that XPC physically interacts with histone H3 and this interaction is negatively regulated by acetylation of the histone protein [47]. Moreover, in living cells, inhibition of histone deacetylases compromises GG-NER, and deacetylation of histones appears to occur around sites with UV-induced DNA damage.…”
Section: Uv-ddb and Chromatin Structuresmentioning
confidence: 99%